A study on the characterization of baobab (Adansonia digitate) fruit seed oil - Abdalkreem, Sara Babiker; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Alam, Md. Zahangir; Marikkar, Mohammed Nazrim (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Baobab (Adansonia digitata L.), is a tree belonging to the Malvaceae plant family. It is widespread throughout the hot, drier regions of tropical Africa. It is a deciduous, massive and majestic tree up to 25 m high, which may live for hundreds of years. Baobab is an important commodity which is integral to the livelihood of rural communities in Africa. The global demand for baobab raw material (e.g. seed oil, fruit pulp) by the food and beverage, nutraceutical and cosmetic industries has increased dramatically in recent years thereby increasing the commercial value and importance of this desired African tree. The baobab fruit contains pulp and seeds. The oil extracted from seed is used by local people as a source of food, energy, medicine and for cosmetic applications. It has been used in the production of lubricants, soaps and personal care products, as well as in the topical treatment of various conditions such as hair dandruff, muscle spasms, varicose veins and wounds. Baobab seed oil had been commonly used for skin care application since ancient times. However, during the last century, synthetic substitutes have become available and have been used to replace natural seed oils. Due to toxic effects of synthetic oils, there is a growing trend to replace them and revert to the use of natural oils in the cosmetic and pharmaceutical industries. The oil extractions from the seeds were carried out using Soxhlet apparatus and n-hexane as solvent. The result showed that the baobab seeds contain 23% oil in average. The Iodine Value (IV) was found to be 75 – 96 g/100g KOH, Free Fatty Acid (FFA) was 2 – 4 % as oleic acid, Saponification Value (SV) was 180 - 195 and fatty acid composition were done for oil characterization; according to this characterization result obtained proved that Baobab seed oil is suitable as edible oil as well as it is suitable for cosmetics and other personal care products.